Effects Of Use Generating Interaction Method Between Schemata And Text (Gist) On Reading Comprehension, And Learning Motivationself-Efficacy Class III Students At SD Negeri Serang 03 - Yuliyani, Dewi; Rusilowati, Ani; Sumarni, Woro (Program Studi PGSD FIP UNM, 2023)
Low reading comprehension can have a negative impact on students' motivation and self-efficacy. Students with low reading comprehension skills often have difficulty understanding the material presented, so they may feel unable to understand the material. This study aims to examine the effect of using the approachGenerating Interaction Between Schemata and Text (GIST) on reading comprehension, learning motivation, and self-efficacy of third grade students at SD Negeri Serang 03. The research methodology used in this study was the use of quantitative methods during data collection and analysis. Data collection was carried out using a quasi-experimental design withpretest-posttest control group design. The use of this method can help students better understand reading, increase self-confidence in learning, and increase learning motivation. This positive and constructive feedback can help students feel more confident about their ability to learn and achieve their learning goals. Overall, this research makes an important contribution to the development of teaching methods that effectively improve students' reading comprehension, learning motivation, and self-efficacy. In addition, this research also provides information and advice for teachers and policy makers to choose appropriate learning methods to improve the quality of education in Indonesia.